LAW ENFORCEMENT ON CONFISCATION OF CORPORATE ASSETS AS AN EFFORT TO RECOVER STATE FINANCES IN CRIMINAL ACTS OF CORRUPTION - Tubalawony, Agnasia Marliana; Chandra, Tofik Yanuar; Kristiawanto, Kristiawanto (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Asset forfeiture in corruption is an important legal enforcement instrument that aims not only to punish perpetrators but also to recover state financial losses. Perpetrators of corruption crimes are not only individuals but also corporations, both legal and non-legal entities. The research problems in this study are: how the regulation of corporate asset forfeiture as an effort to recover state financial losses in corruption crimes is formulated and how the enforcement of corporate asset forfeiture is carried out as a means of recovering state financial losses in corruption crimes. The theories employed in this study include law enforcement theory and asset forfeiture theory. This research applies a normative juridical method with an approach based on legislation, legal doctrines and relevant case studies. The results show that corporate asset forfeiture is a strategic measure which has to be a priority in the law enforcement agenda against corruption. Although Indonesia already has several legal instruments governing asset forfeiture, in reality, the implementation is still hindered by various challenges, such as regulatory, institutional and inter-agency coordination. Law enforcement often emphasizes the ultimum remedy approach, resulting in criminal sanctions against corporations to be overlooked and replaced by administrative sanctions. In fact, criminal prosecution of corporations is not only important as the state's measure to penalize crime, but also serves to restore state financial losses through seizure and confusion of illegal profits. This study recommends strengthening regulations through the enactment of the Asset Forfeiture Bill, enhancing the capability of law enforcement officers in understanding the concept of corporate crime and establishing a special agency to handle asset forfeiture professionally and transparently.